ASURANSI KESEHATAN DAN MANAGED CARE - Anas Khaery; Alpin Putra Amin; Muhammad Sahiril; Rizaldi Sultani; Liza Safitri; Septiani Hartiwi; Juliana Safitri; Resti; Lale Ajeng Khalifatun Wardani (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
Health Insurance is a type of insurance product that specifically guarantees the health or care costs of insurance members if they fall ill or have an accident. Managed care is a health service financing system that is structured based on the number of registered members with control starting from service planning and includes contracts with health service providers for comprehensive services.